PENGARUH KADAR AIR TANAH DAN BOKASHI DAUN GAMAL TERHADAP PERTUMBUHAN VEGETATIF TANAMAN SORGUM (Sorghum Bicolor L.) - Hasyim, Syafria; Hasanah, Uswah; Monde, Anthon; Prahastuti, Sri Wahidah (AGROTEKBIS, 2018)
The research aimed at determining the vegetative growth of sorghum (Sorghum bicolorL.) grown under various rate of gamal leaf bokashi and soil water content. The research was arranged using a two-factorial completely randomized design in which each experimental unit had three replicates. Three different rates of the gamal leaf bokashi were applied i.e. with no bokashi added(b0), 20 t/ha bokashi(b20), and 40 t/ha bokashi (b40). Similarly, three different levels of water contents were implemented i.e. water content equal to 100% field capacity (k100), 75% field capacity (k75) and 50% field capacity (k50). Variable observed were number of leaf, fresh dan dried plant weight, fresh and dried root weigh and soil bulk density. Interaction between the bokashi with the water content significantly affected all variable observed. In general, the plant growth either under the 75%or 50% field capacity water content were not significantly reduced compared to those growth under the 100% field capacity water content as long as the rate of bokashi was 20 t/ha. Soil bulk density increased with increased the bokashi rates at various water contents. Keywords: Gamalleaf bokashi, Soil field capacity and Sorghum.